Understanding and managing conflict: a prerequisite for post-merger FET colleges - Mestry, Raj; Grobler, Bennie; Bosch, Mark (South African Journal of Higher Education, 2016)
It was common practice in the pre-1994 South Africa that many historical black universities and Further Education and Training (FET) colleges were deeply entangled in ongoing conflict, instability and crisis. The academic and administrative staff was in constant conflict with senior management while councils were also deeply divided among themselves, especially on the issue of governance and management. As a result of political changes in South Africa in 1994, the government proposed that the higher education system should be restructured to address past inequalities. Subsequent investigations into restructuring the education system resulted in a wave of mandated mergers across the sector. The Department of Education made provision for the merging of technical colleges by addressing the social structural inequalities manifested through apartheid, and ensuring that limited resources are effectively and efficiently utilized. However, FET mergers introduced a number of organizational changes and dynamics resulting in heightened emotions, fear of job losses, having to move sites, and changes to conditions of service that were unfavourable. Using a questionnaire, this study investigated the perceptions of academic staff on how managers and management teams handled conflict in post-merger FET colleges. The empirical findings included lack of conflict management skills, poor communication and lack of participative decision-making amongst role-players. The Conflict Resolution Model was developed to provide a substantial basis for assisting managers to effectively manage conflict during future FET merging processes, or at newly merged institutions.